ЭССЕ ЖАНРЫНЫҢ ТЕОРИЯЛЫҚ ТИЙКАРЛАРЫ - Матимов, Кошкарбай Генжебаевич (FAN va JAMIYAT, 2026)
The article analyzes the theoretical definition of the essay genre, its emergence, and stages of formation. Thus, the article states that in contemporary literature, the elements of essayistic thinking are noticeable in all genres, transforming into a poetic direction, a continuous transformation is taking place in this direction, and the study of the trend of essay writing in prose works has become one of the pressing issues.